Parental Involvement in Fostering The Character of Childrens’ Discipline at Elementary School - Ismail, Ismail; Busa, Yunus; Tini, Tini (FKIP Universitas Lampung, 2018)
Parental involvement in fostering the character of child discipline in school. Objectives: The purpose of this study is to explore the role that parents play in improving the character of children’s discipline in school. Methods: The study population consisted of 7 elementary schools with a target sample consisting of 8 school personnel and 27 parents. Data were collected using questionnaires and interviews to be analyzed qualitatively and quantitatively. Findings: The most common problem at school is the dynamics of child discipline. The discipline of parents in their children’s education can improve discipline, self-esteem, cognitive development, social interaction skills, and academics as a whole. The role of parents in encouraging student discipline, it is clear that parents must be involved as shown by most respondents (66.67% of parents and 62.50% of teachers). Conclusions: Designing interventions aimed at harmonizing parental and teacher assessments in certain activities related to primary school education will be beneficial in fostering child discipline character education. The results of this study also have implications for child care and protection.Keywords: Parental involvement, school personnel, children’ discipline. DOI: http://dx.doi.org/10.23960/jpp.v8.i2.201807